Advances in Web and Network Technologies and Information Management AP Web/WAIM 2009 International Workshops: WCMT 2009, RTBI 2009, DBIR-ENQOIR 2009, and PAIS 2009 - Chen, Lei; Liu, Chengfei; Zhang, Xiao; Wang, Shan; Strasunskas, Darijus; Tomassen, Stein L.; Rao, Jinghai; Li, Wen-Syan; Candan, K. Selçuk; Chiu, Dickson K. W.; Zhuang, Yi (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This volume comprises papers from four APWeb/WAIM 2009 workshops, which are 1. International Workshop on Web-based Contents Management Technologies (WCMT 2009), 2. International Workshop on Real-Time Business Intelligence (RTBI 2009), 3. International Workshop on DataBase and Information Retrieval and Aspects in Evaluating Holistic Quality of Ontology-based Information Retrieval (DBIR-ENQOIR 2009), as well as 4. International Workshop on Process Aware Information Systems (PAIS 2009. These four workshops were selected from a public call-for-proposals process. The workshop organizers have put a tremendous amount of effort into soliciting and selecting research papers with a balance of high quality and new ideas and new applications.